Influence of virtual reality simulation (excluding augmented reality) on endodontic learning experiences of undergraduate dental students: a systematic review - Muhammad Qasim Javed; Bilal Arjumand; Shaul Hameed Klarkodi; Sundus Atique; Ayman M. Abulhamael; Muhammad Sohail Zafar (BMC Medical Education)
Abstract Background Virtual Reality (VR) technology has demonstrated a promising prospect for enhancing endodontic learning in undergraduate dental students by boosting their procedural skills, accuracy, and confidence. Aim To systematically evaluate the effectiveness of virtual reality (VR) simulation in endodontic education among undergraduate dental students, with a specific focus on four key outcomes: procedural accuracy, enhancement of student confidence, reduction in procedural errors, and overall learner satisfaction. Methods An exhaustive literature search was carried out in December 2024 in PubMed, Cochrane Library, Embase, Scopus, and ClinicalTrials.gov. Randomized controlled trials (RCTs), quasi-experimental studies, and cross-sectional studies published between 2010 and 2024 were included in the review. Risk of bias was appraised as follows: Cochrane Risk of Bias 2.0 (RoB2) tool for RCTs; Newcastle-Ottawa Quality Assessment Scale adapted for cross-sectional studies; National Institute of Health (NIH) Quality Assessment Tool for before-and-after studies; and the Methodological Index for Non-Randomized Studies (MINORS) tool for non-randomized studies without a comparator group. Results Fifteen studies were included in the final analysis. VR-based training showed statistically significant differences between the pre and post-test scores regarding procedural accuracy and efficiency for tasks at the end of endodontics. These results showed that VR training leads to greater confidence and skill levels in students than traditional approaches, improved retention of knowledge, and a reduction in errors. Advantages notwithstanding, limitations around cost and accessibility were observed. Conclusion VR simulation is an effective, valuable tool in the endodontic education toolbox. Further studies should assess cost-effectiveness and long-term clinical performance effects.